2021
DOI: 10.1111/jvp.13032
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetic characteristics of sulfadiazine in channel catfish (Ictalurus punctatus) following oral and intravenous administrations

Abstract: This study aimed to determine the bioavailability and pharmacokinetic parameters of sulfadiazine (SDZ) in channel catfish (Ictalurus punctatus) following oral gavage and intravenous injection. The healthy channel catfish were orally and intravenously administrated with SDZ solution at doses of 50 and 5 mg/kg, respectively. Plasma samples were determined by ultra‐performance liquid chromatography with an ultraviolet detector. The results demonstrated that the concentration‐time profile of SDZ after oral dosing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
3
1
Order By: Relevance
“…The V_F of SDZ in channel catfish were, respectively, 0.53 L/h at 18°C and 1.48 L/h at 24°C, suggesting that the distribution of SDZ in warm water is wider than in cold water. A similar value of 1.60 L/h has been reported in the same species at 24°C via the same oral gavage (Xu, Fu, et al, 2022). In grass carp, the V_F of SDZ (0.93 L/h) was higher than that in channel catfish at 18°C, but the V_F value at 24°C is comparable to that in channel catfish (Xu, Li, et al, 2022).…”
Section: Ta B L Esupporting
confidence: 85%
See 3 more Smart Citations
“…The V_F of SDZ in channel catfish were, respectively, 0.53 L/h at 18°C and 1.48 L/h at 24°C, suggesting that the distribution of SDZ in warm water is wider than in cold water. A similar value of 1.60 L/h has been reported in the same species at 24°C via the same oral gavage (Xu, Fu, et al, 2022). In grass carp, the V_F of SDZ (0.93 L/h) was higher than that in channel catfish at 18°C, but the V_F value at 24°C is comparable to that in channel catfish (Xu, Li, et al, 2022).…”
Section: Ta B L Esupporting
confidence: 85%
“…This may be due to the difference in the excretion of phytophagous fish with omnivorous fish (Xu, Cheng, et al, 2021). A relatively lower value (0.038 L/h/kg) was presented in our previous study at 24°C (Xu, Fu, et al, 2022). It is reported that individuals can exhibit different metabolic profiles caused by microbiota, nutritional input, the interplay of genetic background, and other environmental factors, thereby presenting different body clearances (Braun, 2017; Montgomery et al, 2013; Visconti et al, 2019).…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…In severe cases, headache, abdominal pain, and hand-foot syndrome will occur ( Kaur et al, 2021 ; Otani et al, 2021 ; Platini et al, 2021 ). Moreover, due to its hydrophobicity, oral administration as the only option induces short half-life ( Xu et al, 2021 ). Besides these side effects, the high cost and ease to generate resistance further limit the extensive use of molecular targeted drugs ( Liu et al, 2021 ; Sun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%